Access to health services in tuberculosis patients from the perception of health managers. - León Cabrera, Pablo; Garcias Milian , Ana Julia; Pría Barros, 2María del Carmen; Perdomo Victoria, Irene; Galindo Reymon, Kenia; Figueredo Medina, Yusimi (Horizonte Sanitario, 2021)
Objective: to investigate direct perceptions of access to health services in patients with pulmonary tuberculosis. Methodo: descriptive research with a qualitative approach, in key informants selected intentionally not randomly based on relevant inclusion criteria. The Heads of the Prevention and Control Program for Pulmonary Tuberculosis and HIV / AIDS, at the national and provincial level, were selected. An interview guide was developed and validated by experts, with aspects of access to health services. This was done in optimal conditions and your consent to record was requested. The analysis of information content was organized according to Bardin's methodology, pre-analysis, exploration of the material and treatment of the results and interpretation. Results: There were perceptions by managers of alterations in the dynamics of care, opportunity and its continuity, education to the community and coworkers, involvement of population groups with social indiscipline, existence of social stigmas towards the disease, low participation of the sectors of the community to solve their difficulties, impossibility of always assuming food and transportation, the quality of human resources and program management. Conclusions: The directors of the tuberculosis prevention and control program perceived that there are difficulties in the availability, accessibility, acceptability and quality of health services in patients with pulmonary tuberculosis, these identified elements can contribute to the redesign of the strategy of Elimination of the disease in Havana.